Understanding lignin gasification in supercritical water using reactive molecular dynamics simulations. (December 2020) - Liu, Xiangyang; Wang, Tao; Chu, Jianchun; He, Maogang; Li, Qibin; Zhang, Ying
Abstract: Understanding the micro-mechanism of lignin gasification in supercritical water is meaningful for improving the energy conversion efficiency of biomass. In this work, the molecular model of guaiacyl dimer lignin with γ-O-4 linkages is built and the gasification processes of it in supercritical water at 9 different temperatures between 2000 K and 6000 K are studied by ReaxFF molecular dynamics simulations for the first time. The cleavage mechanism of γ-O-4 lignin and the generation pathways of gases were analyzed. During the gasification process of γ-O-4 lignin, H2 and CO are abundantly generated, while supercritical water contributes the most H and O molecules for them. Temperature are found to play important role in the products and rate of the cleavage of lignin. Highlights: Molecular model of guaiacyl dimer lignin with γ-O-4 linkages is built. Gasification process of lignin in supercritical water is studied by ReaxFF MD. Effects of temperature and supercritical water on lignin cleavage is analyzed. Generation pathways of the main gaseous products are obtained.